Surgical resection of extramedullary haematopoiesis in the posterior mediastinum. Issue 7 (6th September 2018) - Matsumoto, Ryoichi; Yoshiyama, Koichi; Yokoyama, Shintaro; Mitsuoka, Masahiro; Takamori, Shinzo; Akagi, Yoshito
Abstract : Extramedullary haematopoiesis is a rare disease that is usually associated with haematologic disorders such as thalassemia, myelodysplastic syndrome, and hereditary spherocytosis. It frequently occurs in the liver, spleen, and lymph nodes. Rarely, it occurs in the posterior mediastinum. We report the case of a 59‐year‐old man with lateral posterior mediastinal masses that were incidentally detected during treatment for hereditary spherocytosis. We performed video‐assisted thoracic surgery to confirm the diagnosis and differentiate the masses from neurogenic tumours and other posterior mediastinal diseases. The pathological findings were consistent with intrathoracic extramedullary haematopoiesis. Although extramedullary haematopoiesis can be managed without interventions, surgery may be required in some cases. In such cases, video‐assisted thoracoscopic surgery is advised because it is a useful and less invasive procedure. Abstract : This is a report of the case of a patient in whom lateral posterior mediastinal masses were incidentally detected during treatment for hereditary spherocytosis. We performed a video‐assisted thoracic surgery. The pathological findings were consistent with intrathoracic extramedullary haematopoiesis.